Design, synthesis, and evaluation of Bothrops venom serine protease peptidic inhibitors - Silva,Gloria Maria da (2021)
Abstract Background: In Central and South America, snakebite envenomation is mainly caused by Bothrops spp. snakes, whose venoms feature significant biochemical richness, including serine proteases. The available bothropic antivenoms are efficient in avoiding fatalities, but do not completely neutralize venom serine proteases, which are co-responsible for some disorders observed during envenomation. Methods: In order to search for tools to improve the antivenom’s, 6-mer peptides were designed based on a specific substrate for Bothrops jararaca venom serine proteases, and then synthesized, with the intention to selectively inhibit these enzymes. Results: Using batroxobin as a snake venom serine protease model, two structurally similar inhibitor peptides were identified. When tested on B. jararaca venom, one of the new inhibitors displayed a good potential to inhibit the activity of the venom serine proteases. These inhibitors do not affect human serine proteases as human factor Xa and thrombin, due to their selectivity. Conclusion: Our study identified two small peptides able to inhibit bothropic serine proteases, but not human ones, can be used as tools to enhance knowledge of the venom composition and function. Moreover, one promising peptide (pepC) was identified that can be explored in the search for improving Bothrops spp. envenomation treatment.